Henry Sigerist y José Joaquín Izquierdo: dos actitudes frente a la historia de la medicina en el siglo XX - Castañeda López, Gabriela; Rodríguez de Romo, Ana Cecilia (El Colegio de México, A.C., 2007)
Through the correspondence of the historians Henry Sigerist and José Joaquín Izquierdo between 1937 and 1957, this paper seeks to make an interpretation of the history of medicine. It presents brief biographical data and an analysis of these two attitudes regarding history, in order to identify their relevance and impact on the development of the history of medicine, which had reached certain degree of professionalization in the United States and was barely giving its first steps in Mexico. The authors  also comment  on the correspondence and analyze each historian's viewpoint, thus revealing that despite their different place of origin, they shared certain educational traits and a common interest: the consolidation of the history of medicine as a field in itself.